School Inclusion in Children and Adolescents with Autism Spectrum Disorders in France: Report from the ELENA French Cohort Study - Rattaz, Cécile; Munir, Kerim; Michelon, Cécile; Picot, Marie-Christine; Baghdadli, Amaria (Journal of autism and developmental disorders, 2020)
Children and adolescents with ASD are increasingly included in regular school settings, however little is known about how placement decisions are made. In the present study, we examined the types and duration of school attendance among children and adolescents in the ELENA Cohort, a multi-center study of children and adolescents with ASD, ages 2–16 years, in France. Results showed that 88% of subjects were attending school and that children and adolescents with more severe adaptive and cognitive deficits were less likely to attend school. The results provide a topography on school inclusion and ASD in France. Challenging behaviors and sensory processing difficulties were associated with partial-inclusion; and co-occurring anxiety symptoms were associated with inclusion on a full-time basis.